2022
DOI: 10.3390/ijerph19105790
|View full text |Cite
|
Sign up to set email alerts
|

A Guideline for Contextual Adaptation of Community-Based Health Interventions

Abstract: In Southeast Asia, community-based health interventions (CBHIs) are often used to target non-communicable diseases (NCDs). CBHIs that are tailored to sociocultural aspects of health and well-being: local language, religion, customs, traditions, individual preferences, needs, values, and interests, may promote health more effectively than when no attention is paid to these aspects. In this study, we aimed to develop a guideline for the contextual adaption of CBHIs. We developed the guideline in two stages: firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Studies conducted in community settings have found that PH is primarily used as a shared framework to facilitate joint efforts by citizens and local professionals in disadvantaged neighbourhoods to initiate health-promoting initiatives in each of the dimensions of PH [ 35 , 56 , 73 ]. The findings of a qualitative analysis revealed that the use of PH effectively facilitated the achievement of these objectives, catalysing an ongoing trend of transformation within neighbourhoods.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in community settings have found that PH is primarily used as a shared framework to facilitate joint efforts by citizens and local professionals in disadvantaged neighbourhoods to initiate health-promoting initiatives in each of the dimensions of PH [ 35 , 56 , 73 ]. The findings of a qualitative analysis revealed that the use of PH effectively facilitated the achievement of these objectives, catalysing an ongoing trend of transformation within neighbourhoods.…”
Section: Resultsmentioning
confidence: 99%